Costs and cost‐effectiveness of a collaborative data‐to‐care intervention for HIV treatment and care in the United States. Issue 1 (22nd January 2023) - Shrestha, Ram K.; Fanfair, Robyn Neblett; Randall, Liisa M.; Lucas, Crystal; Nichols, Lisa; Camp, Nasima; Brady, Kathleen A.; Jenkins, Heidi; Altice, Frederick L.; DeMaria, Alfred; Villanueva, Merceditas; Weidle, Paul J.
Abstract: Introduction: Data‐to‐care programmes utilize surveillance data to identify persons who are out of HIV care, re‐engage them in care and improve HIV care outcomes. We assess the costs and cost‐effectiveness of re‐engagement in an HIV care intervention in the United States. Methods: The Cooperative Re‐engagement Control Trial (CoRECT) employed a data‐to‐care collaborative model between health departments and HIV care providers, August 2016–July 2018. The health departments in Connecticut (CT), Massachusetts (MA) and Philadelphia (PHL) collaborated with HIV clinics to identify newly out‐of‐care patients and randomize them to receive usual linkage and engagement in care services (standard‐of‐care control arm) or health department‐initiated active re‐engagement services (intervention arm). We used a microcosting approach to identify the activities and resources involved in the CoRECT intervention, separate from the standard‐of‐care, and quantified the costs. The cost data were collected at the start‐up and recurrent phases of the trial to incorporate potential variation in the intervention costs. The costs were estimated from the healthcare provider perspective. Results: The CoRECT trial in CT, MA and PHL randomly assigned on average 327, 316 and 305 participants per year either to the intervention arm ( n = 166, 159 and 155) or the standard‐of‐care arm ( n = 161, 157 and 150), respectively. Of those randomized, the number of participants re‐engaged in care within 90 days in the intervention and standard‐of‐care arms was 85 and 70 in CT, 84 and 70 in MA, and 98 and 67 in PHL. The additional number of participants re‐engaged in care in the intervention arm compared with those in the standard‐of‐care arm was 15 (CT), 14 (MA) and 31 (PHL). We estimated the annual total cost of the CoRECT intervention at 490, 040 in CT, 473, 297 in MA and 439, 237 in PHL. The average cost per participant enrolled was 2952, 2977 and 2834 and the average cost per participant re‐engaged in care was 5765, 5634 and 4482. We estimated an incremental cost per participant re‐engaged in care at 32, 669 (CT), 33, 807 (MA) and 14, 169 (PHL). Conclusions: The costs of the CoRECT intervention that identified newly out‐of‐care patients and re‐engaged them in HIV care are comparable with other similar interventions, suggesting a potential for its cost‐effectiveness in the US context.